E-BUSINESS DAN EFEKTIVITAS PROSES BISNIS: PERAN SISTEM INFORMASI DALAM ERA DIGITAL - ELYSA RAHMAYANI; Muhammad Irwan Padli Nasution (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2024)
E-business has revolutionized the way companies operate in the digital era, changing traditional business processes to become more efficient and responsive. This article discusses the effectiveness of business processes in the context of e-business and the crucial role of information systems in improving operational performance. By utilizing information technology, companies can automate processes, integrate systems, and analyze data for better decision making. While there are challenges, such as data security and implementation costs, the benefits derived from implementing information systems—including better data management, efficient communications, and improved customer experience—make them essential for business success in the digital era. This research emphasizes the importance of continuous adaptation and innovation to face ever-changing market dynamics.